Kualitas Eksternal Telur Ayam Ras Komersil Di Pasar Tradisional Sentani Kabupaten Jayapura - Tharukliling, Selvia (Universitas Islam Kadiri, 2024)
Abstract The research was conducted at the Sentani traditional market. This research aims to determine the level of quality of commercial chicken eggs circulating in the Sentani traditional market externally (in terms of egg shape, egg weight and egg shell cleanliness). The research method used is a survey method by making direct observations and measurements of the research object. Determination of the sample using purposive sampling technique. The results of the research show that the shapes of eggs circulating in the old market and the new market in Sentani, in order from the largest to the smallest in number, are oval, spherical, conical and biconical. The weight of eggs circulating in both markets falls into the medium and large categories. Meanwhile, the quality of egg shells from these two markets is dominated by quality A, quality AA and quality B. Externally, the best quality is in the local eggs from jayapura. Keywords: purebred chicken eggs, external quality, traditional markets